1959
DOI: 10.1079/bjn19590061
|View full text |Cite
|
Sign up to set email alerts
|

The mode of action of dietary carbohydrate on protein metabolism

Abstract: It was recognized more than 60 years ago that administration of carbohydrate to fasting animals causes a fall in urinary nitrogen output, whereas the giving of fat does not have a similar effect (see review of literature by Munro, 1951). In confirmation of this difference between the actions of carbohydrate and fat, the giving of glucose to fasting subjects causes a sharp and transient fall in blood amino-acid concentration, which does not occur after the administration of fat (Munro & Thomson, 1953). Thus car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1962
1962
2009
2009

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The decrease in concentration of plasma EAA was primarily due to reduced supply of these amino acids but it was also related to energy supply, because addition of extra energy to the low-egg-protein diet resulted in reduction of plasma EAAs. Further evidence that decrease in the levels of plasma EAAs in protein deficiencies may be intensified by supply of excess energy is as MA FREE AMINO ACIDS IN MEN 305 follows: (i) LUNN et al (8) observed hyperinsulinemia resulting from ingestion of high-carbohydrate meals during the early stage of kwashiorkor and suggested that utilization of amino acids in tissues was enhanced in this condition; (ii) We found previously (9) that the nitrogen balance and NPU observed with submaintenance N intakes were greatly affected by the protein sparing effect of energy intake; (iii) MUNRO et al (20) showed that the lowered levels of plasma amino acids observed in subjects loaded with glucose were due to enhanced utilization of the amino acids in the muscle through the action of insulin; and (iv) recently, GRIMBLE and WHITEHEAD (7) also reported similar findings to (iii), in patients with kwashiorkor after administration of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in concentration of plasma EAA was primarily due to reduced supply of these amino acids but it was also related to energy supply, because addition of extra energy to the low-egg-protein diet resulted in reduction of plasma EAAs. Further evidence that decrease in the levels of plasma EAAs in protein deficiencies may be intensified by supply of excess energy is as MA FREE AMINO ACIDS IN MEN 305 follows: (i) LUNN et al (8) observed hyperinsulinemia resulting from ingestion of high-carbohydrate meals during the early stage of kwashiorkor and suggested that utilization of amino acids in tissues was enhanced in this condition; (ii) We found previously (9) that the nitrogen balance and NPU observed with submaintenance N intakes were greatly affected by the protein sparing effect of energy intake; (iii) MUNRO et al (20) showed that the lowered levels of plasma amino acids observed in subjects loaded with glucose were due to enhanced utilization of the amino acids in the muscle through the action of insulin; and (iv) recently, GRIMBLE and WHITEHEAD (7) also reported similar findings to (iii), in patients with kwashiorkor after administration of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Munro, Black & Thomson (1959) have suggested that carbohydrate causes deposition of amino acids in the muscles, with reduction of liver protein. The liver is generally accepted as the site of serum-albumin production and the above suggestion might explain the increased rate of fall of serum albumin in animals fed on the higher carbohydrate diets at suboptimal intakes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, nitrogen retention dose not necessarily mean protein anabolism only, such as synthesis of protein. It has been reported that the protein-sparing action might be attributable to protein synthesis in the muscle (18). However, the reduction of urinary nitrogen excretion would be involved in more complicated biochemical changes.…”
Section: Discussionmentioning
confidence: 99%